2022
DOI: 10.1155/2022/7396950
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Systemic Rehabilitation Nursing Combined with WeChat Publicity and Education on the Early Cognitive Function and Living Quality of the Patients with Cerebral Arterial Thrombosis

Abstract: Objective. To investigate the effects of systemic rehabilitation nursing combined with WeChat publicity and education on the early cognitive function and living quality of the patients with cerebral arterial thrombosis. Methods. Ninety-two patients with cerebral arterial thrombosis treated in our hospital (January 2019–January 2021) were selected as the research objects and equably divided into control group and study group according to their nursing model, with 46 patients in each group. The control group rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Quality of life. The 36-item short form health survey (SF-36) [ 13 ] was adopted to evaluate the patients' health, which was developed by the Boston Health Research Institute in the United States and has been widely used in the areas of quality of life measurement in the general population, evaluation of the effects of clinical trials, and health policy assessment. The modified scale mainly included four dimensions of general health, physical functioning, social functioning, and mental health.…”
Section: Methodsmentioning
confidence: 99%
“…Quality of life. The 36-item short form health survey (SF-36) [ 13 ] was adopted to evaluate the patients' health, which was developed by the Boston Health Research Institute in the United States and has been widely used in the areas of quality of life measurement in the general population, evaluation of the effects of clinical trials, and health policy assessment. The modified scale mainly included four dimensions of general health, physical functioning, social functioning, and mental health.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate an infarction site located in a functionally important brain region or a larger lesion, which results in poor prognosis due to serious neurological deficits (Lu et al., 2022). Neurological function recovery is enormous importance to stroke patients because the deterioration of neurological function affects their cognitive, sensory, and motor functions directly (Jin et al., 2022; Wang et al., 2018). In this study, our results indicated that EA may be a promising treatment for improving neurological deficits after ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, self-efficacy is a theory of self-confidence that looks at an individual’s ability to deal with various pressures in life. The General Self-Efficacy Scale (GSES) 15 was used to score the self-efficacy of patients before and one month after nursing. The score ranged from 0 to 4, and the lower the score, the worse the self-efficacy of patients.…”
Section: Methodsmentioning
confidence: 99%